Fractal character of the SAXS correlation volume in poly(ethylene glycol)/silica hybrid wet gels - Donatti, Dario A. [UNESP]; Vollet, Dimas R. [UNESP]; Ruiz, Alberto Ibanez [UNESP] (Springer, 2010)
Small-angle X-ray scattering (SAXS) was employed to study the nanostructural properties of poly(ethylene glycol)(PEG)/silica hybrid wet gels prepared from hydrolysis of tetraethoxysilane (TEOS) in mixtures with PEG/(PEG + TEOS) molar ratio in the nominal range between 0 and 0.8. The SAXS pattern was found to be well fitted by the scattering from a polymeric particle of radius of gyration R (g) with an internal structure of primary silica particles described by a polymeric constraint of a mass-fractal of dimension D. R (g) increases with the PEG quantity while D first increases from 2.24 for the pure TEOS-derived gel to reach values between 2.46 and 2.40 with the additions of PEG. The correlation volume V (c) as determined by SAXS for such a polymeric structure behaves as a volume-fractal and accordingly scales with R (g) as V (c) similar to R (g) (D) . An overall mean value of about 1 nm could be estimated as an upper limit for the radius of the primary silica particle building up the structure of all the wet gels, independent of the PEG addition.
Keywords: SAXS; PEG/silica hybrid gels; Volume-fractal